2022
DOI: 10.3389/fnins.2022.927111
|View full text |Cite
|
Sign up to set email alerts
|

Brain and brain-heart Granger causality during wakefulness and sleep

Abstract: In this exploratory study we apply Granger Causality (GC) to investigate the brain-brain and brain-heart interactions during wakefulness and sleep. Our analysis includes electroencephalogram (EEG) and electrocardiogram (ECG) data during all-night polysomnographic recordings from volunteers with apnea, available from the Massachusetts General Hospital’s Computational Clinical Neurophysiology Laboratory and the Clinical Data Animation Laboratory. The data is manually annotated by clinical staff at the MGH in 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
1
1
Order By: Relevance
“…Several previous studies have employed Granger causality or similar methods to examine directional interactions between EEG and heart rate, raw EKG, or HRV power time series. Contrary to results of the present study, the majority of these studies have reported stronger brain-to-heart than heart-to-brain effects (Abdalbari et al, 2022; Greco et al, 2019; Lin et al, 2016; Pardo-Rodriguez et al, 2021). However, one study showed that HF-HRV power changes preceded changes in the delta band during sleep (Jurysta et al, 2003), and another showed stronger heart-to-brain interactions during an emotion elicitation paradigm (Candia-Rivera et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
“…Several previous studies have employed Granger causality or similar methods to examine directional interactions between EEG and heart rate, raw EKG, or HRV power time series. Contrary to results of the present study, the majority of these studies have reported stronger brain-to-heart than heart-to-brain effects (Abdalbari et al, 2022; Greco et al, 2019; Lin et al, 2016; Pardo-Rodriguez et al, 2021). However, one study showed that HF-HRV power changes preceded changes in the delta band during sleep (Jurysta et al, 2003), and another showed stronger heart-to-brain interactions during an emotion elicitation paradigm (Candia-Rivera et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
“…Granger causality has been used to learn structure from polysomnographic data in previous studies. Orjuela-Cañón et al [8] used Granger causality to study the changes brought about by a session of continuous positive air pressure (CPAP) therapy; Faes et al [10], the impact of sleep stages; Günther et al [11], the impact of sleep stages and apnoea; and Pizzi et al [12] and Abdalbari et al [13], the difference between wakefulness and sleep. These studies all involve substantially fewer subjects than this one.…”
Section: Granger Causalitymentioning
confidence: 99%
“…Twenty seconds is quite a small window length; this was chosen to balance the need for as much data as possible with the requirement for stationarity. Previous studies have used windows of similar length when dealing with physiological signals [12,13].…”
Section: Granger Causality 221 Windowingmentioning
confidence: 99%
“…In neuroscience, Granger causality has been applied to functional magnetic resonance imaging (FMRI) [ 11 , 12 , 13 ], magnetoencephalography (MEG) [ 14 , 15 , 16 ], and local field potentials (LFP) [ 17 , 18 , 19 ]. Abdalbari et al [ 20 ] used Granger causality for sleep data analysis to capture the physiological mechanisms during wakefulness and sleep. Hartmann et al [ 21 ] studied the brain–heart interaction during sleep by using Granger causality to examine the electroencephalography (EEG) frequency bands with cortical and cardiovascular activities.…”
Section: Introductionmentioning
confidence: 99%